Lack of Judges, Lack of Justice? : Evidence from Vacancies at the Czech Constitutional Court - Žáček, Ondřej; Bertoli, Paola; Dušek, Libor; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This thesis deals with the question whether judges at the Constitutional Court of the Czech Republic respond to the increase in average caseload through the change of their decision-making. My model of binding time constraint that restricts judges (and the Constitutional Court) in their output optimization predicts that vacancies along with the Court’s growing workload should rationally lead to more frequent procedural rejections of the constitutional complaints and to the protraction of the length of proceedings. Subsequent empirical tests of dataset that consists of several tens of thousands of cases resolved by the Constitutional Court between 2002 and 2015 tend to only confirm the second aforementioned hypothesis.
Vedoucí práce: Paola Bertoli
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses